Wiara i krew. Porównanie treści religijnych w komiksach Jan Hardy. Żołnierz Wyklęty i Polski Superbohater Biały Orzeł. Kroniki konfliktu - Lara, Magdalena (Humaniora. Czasopismo Internetowe, 2019)
The creators and publishers of patriotic comics pursue social and educational goals – they try to popularize the idea of the national community and solidify national values. They develop variety of means to effectively promote specific attitudes and actions. For this purpose, they use, inter alia, a religious imaginarium, often identified with national symbolism. The analysis of the content of the two most popular patriotic comics – the Biały Orzeł. Kroniki konfliktu and Jan Hardy. Żołnierz Wyklęty – shows differences in using varied religious symbols. The comics by using similar signs shape disparate universe and promote different attitudes. The origin of the superpower separates what is human and divine, at the same time determining the way of understanding the nation. The blood and faith become a medium of Polishness – to save the consistency of the nation, one must care of the proper Catholic attitude and pay attention to the cultural and ethnic heritage.